1969
DOI: 10.1210/jcem-29-3-346
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Growth Hormone. III. Growth Hormone Release in Children with Primary Hypothyroidism and Thyrotoxicosis1

Abstract: Growth hormone release was assessed utilizing insulin-induced hypoglycemia and arginine infusion in 13 children with primary hypothyroidism and in 10 patients with thyrotoxicosis. In the hypothyroid group there were 6 blunted and 7 normal responses, with a mean peak concentration of serum growth hormone (SGH) of 7.9 ng/ml which differed significantly from the controls (p<.02). The hypothyroid patients also exhibited a delayed peak in SGH compared to normal subjects. There was no correlation between the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Spontaneous nocturnal secretion of GH is low in hypothyroidism and hyperthyroidism (27,28). The rate and the amount of GH released are reduced in adolescents with untreated thyrotoxicosis compared with normal controls.…”
Section: Hypothyroidism and Thyrotoxicosismentioning
confidence: 98%
“…Spontaneous nocturnal secretion of GH is low in hypothyroidism and hyperthyroidism (27,28). The rate and the amount of GH released are reduced in adolescents with untreated thyrotoxicosis compared with normal controls.…”
Section: Hypothyroidism and Thyrotoxicosismentioning
confidence: 98%
“…In part, thyroid hormone may exert these effects by stimulating the formation of growth hormone (GH).1 Thus, the levels of radioimmunoassayable pituitary and circulating GH are extremely low in hypothyroid animals (2), and studies ofhypothyroid children indicate that plasma GH response to insulin administration is blunted. The serum GH value, however, does not appear to be as uniformly depressed in hypothyroid patients as in hypothyroid rats (3). Recently, Hervas et al (4) have shown by use of a sensitive radioimmunoassay that the circulating levels of pituitary GH IAbbreviations used in this paper: GH, growth hormone; a-GPD, a-glycerophosphate dehydrogenase; k, plasma concentration yielding half-nuclear occupancy; M, binding capacity; ME, malic enzyme; q, fractional nuclear occupancy; R, responsivity or rate of induction; T3, triiodothyronine.…”
Section: Introductionmentioning
confidence: 73%
“…These doses were selected because they are known to saturate the nuclear sites for the period of the experiment. At designated intervals (3,6,12,16,20, and 24 h) after the injection, rats were killed and pituitary GH content was measured. As shown in Fig.…”
Section: Determination Of Basic Parametersmentioning
confidence: 99%
“…However, various reports including data in humans indicated that THs may also exert inhibitory effects on GH. Children with thyrotoxicosis have normal GH responses to provocative stimuli (Katz et al 1969) but diminished 24-h GH secretion (Finkelstein et al 1974). In hyperthyroid patients, sleep-related GH release is decreased (Sazaki et al 1985).…”
Section: Introductionmentioning
confidence: 99%